Is early cannulation of an arteriovenous fistula associated with early failure of the fistula?. Issue 1 (March 2017) - Wilmink, Teun; Hollingworth, Lee; Stevenson, Tamasin; Powers, Sarah
Objective: To study the effect of early cannulation of arteriovenous fistulas (AVF) on early AVF failure. Methods: Analysis of two databases of access operations and dialysis sessions from 1/12/2002 till 1/4/2015. Follow-up until 1/4/2016. Functional dialysis use defined as six consecutive cannulations of the AVF with two needles. Early cannulation defined as needling of the AVF within 30 days of creation. Early failure was defined as abandonment for new form of access within 90 days of first cannulation. Machine blood-flow rates (BFR) of each dialysis session for the first 2 months collected from the dialysis database. Results: We analysed 1167 AVFs with functional dialysis use. Some 148 AVFs (11%) were needled within 30 days. Early needling was not associated with increased early failure rates (p = 0.43). Early failure rates were lower in AVFs with six consecutive successful cannulations from the start (p = 0.002). There was a trend of reduced early failure rates (test for trend: p = 0.018) in the latter years of the study period, but no trend in early cannulation rates (p = 0.19). Failure to achieve six successful cannulations from the start was an independent predictor of early AVF failure but early needling was not an independent predictor in multivariate analysis. Average starting BFRs were higher in AVF that were needled early. Conclusions: Early cannulation was not associated with early failure. Failure to achieve six successful cannulations from the start was an independent predictor of early failure. The trend in yearly variation of early failure rates suggests that evolving practices influenced early failure rates.